Hyper Brk-Algebras (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this article, BRK-Algebras presents the idea of hyper structure and some related properties are discussed.  In addition, we present the concept of the hyper BRK-ideal of a hyper BRK-algebra. A few characteristics are obtained. Furthermore the concept of homomorphism is generalised to hyper BRK-Algebras